Réduction De L’anxiété De Production Orale - Kalińska, Sylwia (2023)
Research has consistently shown that anxious language students suffer significantly during oral activities and that anxiety has a negative impact on students’ attitudes toward language study. The purpose of this article is to help practitioners better understand some of the variables related to anxiety and oral skills and to offer teachers methods to lower the levels of stress in their classroom through the use of anxiety-management tools and activities that encourage authentic communication within a warm and supportive community of learners.
Keywords: language anxiety; authentic communication; student; foreign language; speaking